To determine whether the points (0, 2) and (0, -4) are solutions to the system of equations \( y = 2x + 2 \) and \( y = 2x - 4 \), we can substitute the x-values of each point into both equations and see if the corresponding y-values match.
-
For the point (0, 2):
-
Substituting \( x = 0 \) in the first equation \( y = 2x + 2 \): \[ y = 2(0) + 2 = 0 + 2 = 2 \] This point lies on the first equation.
-
Substituting \( x = 0 \) in the second equation \( y = 2x - 4 \): \[ y = 2(0) - 4 = 0 - 4 = -4 \] This point does not lie on the second equation.
-
-
For the point (0, -4):
-
Substituting \( x = 0 \) in the first equation \( y = 2x + 2 \): \[ y = 2(0) + 2 = 0 + 2 = 2 \] This point does not lie on the first equation.
-
Substituting \( x = 0 \) in the second equation \( y = 2x - 4 \): \[ y = 2(0) - 4 = 0 - 4 = -4 \] This point lies on the second equation.
-
Since (0, 2) satisfies the first equation but not the second, and (0, -4) satisfies the second equation but not the first, neither point is a solution to the system of equations.
Therefore, the correct response is:
Neither of these points are solutions.